2019
DOI: 10.1177/0363546519866453
|View full text |Cite
|
Sign up to set email alerts
|

Portal Placement and Biomechanical Performance of Endoscopic Proximal Hamstring Repair

Abstract: Background: Proximal hamstring tendon avulsions are debilitating and commonly cause pain, weakness, and functional limitations. Open surgical repair has been the standard, but improved endoscopic techniques have enabled proximal hamstring fixation with decreased risk of infection and numbness, without the morbidity of a large incision. Purpose/Hypothesis: The purpose was to (1) describe pertinent anatomy surrounding the proximal hamstring origin in relation to 4 endoscopic portal sites and (2) test for biomech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
0
7
1
Order By: Relevance
“…A recently published study of endoscopic proximal hamstring repair and portal sites concluded that major neurovascular structures were safely out of the way of all portal site trajectories, with a minimum of 2.4 cm (range 1.3-5.4 cm) to the sciatic nerve and 2.55 cm (range 0.7-6.8 cm) to the posterior femoral cutaneous nerve. 18 The apparent discrepancies with our current study are likely to be related to several factors. Portal marking and placement in our study was performed identically to that originally described and illustrated by Dierckman and Guanche 12 with medial and lateral portals created "2 cm medial and lateral to the palpable ischial tuberosity" and an inferior portal created "4 cm distal to the tip of the ischium and equidistant from the medial and lateral portals".…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…A recently published study of endoscopic proximal hamstring repair and portal sites concluded that major neurovascular structures were safely out of the way of all portal site trajectories, with a minimum of 2.4 cm (range 1.3-5.4 cm) to the sciatic nerve and 2.55 cm (range 0.7-6.8 cm) to the posterior femoral cutaneous nerve. 18 The apparent discrepancies with our current study are likely to be related to several factors. Portal marking and placement in our study was performed identically to that originally described and illustrated by Dierckman and Guanche 12 with medial and lateral portals created "2 cm medial and lateral to the palpable ischial tuberosity" and an inferior portal created "4 cm distal to the tip of the ischium and equidistant from the medial and lateral portals".…”
Section: Discussioncontrasting
confidence: 86%
“…Moreover, a recent cadaveric study of paired pelvic specimens found no biomechanical difference between open and endoscopically repaired proximal hamstring tendons in terms of ultimate load, strain, or displacement at failure. 18 Our data show that of the 3 standard endoscopic portals, the standard lateral portal is indeed the most dangerous, with direct injury to the sciatic nerve in 37% (11/30). Furthermore, more vertical insertion of a pin through a standard lateral portal placed the sciatic and PFC nerves at greatest risk, with direct injury to the sciatic nerve seen in 60% (6/10) of cases whereas no direct injury to the sciatic or PFC nerves was seen with any orientation of pin through a standard medial or inferior portal.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The ischium landmark is outlined on the skin and the central portal is created on the gluteal fold in line with the ischium, as seen on Figure 3 A. Fluoroscopic guidance is used to guide the blunt trocar towards the ischium, to protect the sciatic nerve, which lies approximately 1 to 2 cm lateral to the hamstring origin on the ischium. 14 The lateral portal is created with aid of a spinal needle and direct visualization. A bursectomy with an arthroscopic shaver is made to clear the underlying structures, and a diagnostic endoscopic evaluation is performed, identifying the ischial tuberosity, remaining tendon fibers, and sciatic nerve, as seen in Video 1 .…”
Section: Surgical Technique (With Video Illustration)mentioning
confidence: 99%
“…On regular basis, a medial portal and an accessory portal are created with the same technique as the lateral one with direct visualization, as seen in Figure 3 B. It’s important to keep in mind that the posterior femoral cutaneous nerve divides just above the ischial tuberosity, and the inferior gluteal nerve and artery travel 5 cm proximal to the ischium. 14 The number of anchors is determined according to the tear pattern; fewer than 2 anchors are not recommended. For this case, two 5.5-mm triple-loaded HEALICOIL anchors (Smith & Nephew) were introduced, using its awl and tap.…”
Section: Surgical Technique (With Video Illustration)mentioning
confidence: 99%